2022
DOI: 10.1266/ggs.22-00022
|View full text |Cite
|
Sign up to set email alerts
|

Parallel molecular alteration between Alzheimer’s disease and major depressive disorder in the human brain dorsolateral prefrontal cortex: an insight from gene expression and methylation profile analyses

Abstract: Alzheimer's disease (AD) and major depressive disorder (MDD) are comorbid neuropsychiatric disorders that are among the leading causes of long-term disability worldwide. Recent research has indicated the existence of parallel molecular mechanisms between AD and MDD in the dorsolateral prefrontal cortex (DLPFC). However, the premorbid history and molecular mechanisms have not yet been well characterized. In this study, differentially expressed gene (DEG), differentially co-expressed gene and protein-protein int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In AD, amyloid-β plaques and neurofibrillary tangles are extensively reported substrates that can induce disruption of neural function, culminating in neuronal cell death. A relative increase in non-neuronal cell numbers, both in the cerebral cortex and subcortical white matter, can contribute to the reactive glial cell response to neuronal death ( 21 , 22 ). A number of previous studies have suggested that neurodegenerative diseases are caused by cortical network dysfunction instead of dysregulation in any isolated brain region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In AD, amyloid-β plaques and neurofibrillary tangles are extensively reported substrates that can induce disruption of neural function, culminating in neuronal cell death. A relative increase in non-neuronal cell numbers, both in the cerebral cortex and subcortical white matter, can contribute to the reactive glial cell response to neuronal death ( 21 , 22 ). A number of previous studies have suggested that neurodegenerative diseases are caused by cortical network dysfunction instead of dysregulation in any isolated brain region.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have suggested that neurodegenerative diseases are caused by cortical network dysfunction instead of dysregulation in any isolated brain region. However, the isolated brain regions that are selectively damaged are likely to act as ‘nodes’ in the pathological brain network ( 21-24 ). This was proposed as the ‘network degradation hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDD modulates the initiation and/or episodic symptom exacerbations of most 'autoimmune'/'immune-mediated' disorders, including multiple sclerosis [184], rheumatoid arthritis [183], Alzheimer's disease [185], Parkinson's disease [186] and SLE [187], indicating the role that MDD pathophysiology has in their course. MDD pathophysiology includes gut dysbiosis/permeability, pro-inflammatory cytokines, IDO induction and the conversion of tryptophan to kynurenine, leading to enhanced AhR activation, thereby dysregulating the tryptophan-melatonin pathway [188], and allowing the MDD pathophysiology to be intimately linked to the pathophysiological processes underpinning 'autoimmune' disorders.…”
Section: Autoimmunity and Psychiatric Disordersmentioning
confidence: 99%